2005
DOI: 10.2355/isijinternational.45.1741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Static and Dynamic Mechanical Property of a Dual Phase Steel Studied by Shear Punch Testing

Abstract: The high-speed deformation behavior of a dual phase steel was studied by means of dynamic Hopkinson bar shear punch testing, with an emphasis on the influence of microstructure. Dual phase microstructures with different fractions of martensite were obtained by changing heat treatment parameters during intercritical annealing. The effects of low temperature tempering (170°C, 235°C, and 300°C) and bake hardening treatment (5 % pre-strain followed by holding at 170°C for 20 min) were also investigated for two sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Increasing the holding time increases the austenite volume fraction, which then will transform to martensite upon quenching in the water. Therefore, VM increased with increasing intercritical annealing time, as reported by Qu et al 15) and Azizi-Alizamini et al 12) As shown in Fig. 3(b), microstructural feature of the cold-rolled duplex structure is consisted of high density of ferrite/martensite interfaces which can be nucleation sites for austenite formation (Fig.…”
Section: Microstructuressupporting
confidence: 65%
“…Increasing the holding time increases the austenite volume fraction, which then will transform to martensite upon quenching in the water. Therefore, VM increased with increasing intercritical annealing time, as reported by Qu et al 15) and Azizi-Alizamini et al 12) As shown in Fig. 3(b), microstructural feature of the cold-rolled duplex structure is consisted of high density of ferrite/martensite interfaces which can be nucleation sites for austenite formation (Fig.…”
Section: Microstructuressupporting
confidence: 65%
“…elastic loading to the yield point, plastic deformation, and the ultimate load at failure. In a previous study, 14 a linear relationship between the maximum shear punch force (F max , as shown in Fig. 6) and the ultimate tensile strength (UTS) was found.…”
Section: Typical Shear Punch Curvesmentioning
confidence: 66%
“…Using the modified SHPB, Huang et al (2011) developed a dynamic PS method to quantify the dynamic shear properties of Longyou sandstone. This development followed attempts to investigate the dynamic shear response of ductile materials using the SHPB in combination with the PS method, such as metals (Dabboussi and Nemes 2005;Qu et al 2005) and fiber composites (Li et al 2002). Later, shear properties of various rock and rock-like materials such as Fangshan marble (Yao et al 2017) and concrete (Grima et al 2015) were studied by employing the modified SHPB combined with the PS method.…”
Section: Gsmentioning
confidence: 99%